Unveiling Trends and Insights: A Bibliometric analysis on Social Media Marketing (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
Objective: Significant transformations have taken place in the marketing industry over  the past century. The extent of the transformation in marketing strategies, tools, and  tactics is truly difficult to grasp. In a traditional economy, the market was restricted to  a particular physical space, facing constraints concerning time, location, and utility.  Globalization has led to a significant contraction of the market, bringing it within the  reach of our hands, as all markets are now easily accessible. Initially created as a means  for social interaction, social media has evolved into a powerful instrument for brand  positioning, advertising, and various other aspects of marketing management. Staying  informed about the most recent developments in the marketing and tooling sectors is  essential for any organization. The main objectives of the paper are to enhance readers’  knowledge and to improve their understanding of social media marketing. This study  provides a bibliometric analysis of social media marketing research spanning from  2009 to 2024 to assist scholars in the field.Approach/Methodology/Design: The  Scopus database was employed to examine how research in social media marketing  has developed over the years, to find out the leading authors, countries, documents  and journals in this research domain, to study the keyword occurrence pattern in  the field of social media marketing and to investigate the association between the  citations and co-citations of social media marketing research articles.Results: It has  been noted that the researches in social media marketing were minimal till 2014,  gaining momentum after 2015 and peaking in 2024. Ko, Eunju is found to be most  impactful author whereas Dwivedi, Yogesh K. is most productive author. The country  that has significantly influenced the realm of social media marketing is United States.  Most prominent article is Kozinets titled “Networked narratives: Understanding  word-of-mouth marketing in online communities” and the most impactful journal in  this field is “Journal of Business Research”.
Keywords: Social Media Marketing; Bibliometric analysis